501 A common finding with an atypical (rare) presentation. (17th January 2020) - Rigueira, J; Cunha, N; Ferreira, R; Rodrigues, M; Silva, J; Junqueira, N; Nobre, A; Pinto, F J; Almeida, A G
Abstract: Introduction: Hypereosinophilic syndrome (HES) is characterized by persistent eosinophilia and eosinophil-mediated organ damage. Cardiac thrombosis and thromboembolic complications are common causes of morbidity and mortality in these patients. The echocardiogram is the first method of image in the assessment of cardiac involvement by HES. Clinical Case: An 81 year-old male, with previous history of hypereosinophilia under investigation without specific treatment, presented to the emergency department after several episodes of syncope and exertional dyspnea. The patient denied fever. He was hemodynamically stable and had a holosystolic murmur (III/VI) audible in the entire precordium. The ECG was normal. The blood tests showed leukocytosis (26.69 x10^9/L) mainly related to hypereosinophilia (17.5 x10^9/L), thrombocytopenia (134.000/uL), elevation of troponin (hsTnT= 276 ng/L, normal range <14) and reactive C-protein (3.27mg/dL, normal range <0.5). The transthoracic echocardiogram (limited for the acoustic window) showed a mass in the aortic valve with obstruction of the left ventricle outflow tract (LVOT) during systole (maximum velocity= 3.85m/s, maximum gradient = 59mmHg, mean gradient = 31mmHg), moderate mitral regurgitation, left ventricle hypertrophy with normal ejection fraction and mild pericardial effusion. A transesophageal echo (TEE) was performed confirming the presence of a hyperechogenic sessile mass, with irregular contours, measuring 23x30 mm, attached to the aortic valve causing obstruction of the LVOT (Figure 1 A and B – TEE midesophageal long axis in diastole and systole, respectively; C and D - TEE midesophageal short axis in diastole and systole, respectively). The patient was submitted to emergent cardiac surgery for excision of the mass and aortic valve replacement (Figure 1E and F- intraoperative and macroscopic views of the mass, respectively). The anatomopathological diagnosis confirmed an aortic valve thrombus. Discussion/Conclusion: Native aortic valve thrombosis is a rare situation with severe complications like acute myocardial infarction, peripheral ischemia, stroke, cardiogenic shock and sudden death. In HES, cardiac involvement is present in up to 40-50% of patients, mainly with endomyocardial fibrosis and mural thrombus formation. Native and prosthetic mitral valve thrombosis has also been described, but aortic valve involvement is very unusual. Thrombi are one of the most common intracardiac masses, but here we present a rare case of native aortic valve thrombosis with high risk of sudden cardiac death, possibly related to HES. The echocardiogram, particularly the transesophageal echo was essential for the identification of the mass and surgical planning, but as usual in intracardiac masses, the final diagnosis was histological.